An overview of the potential of Citrus hystrix (kaffir lime) essential oil as mosquito repellent - Nurul Asyikin Md Zaki; Junaidah Jai; Izzat Syahmi Kamal Shahrizan; Dewi Selvia Fardhyanti; Megawati Megawati; Nadya Alfa Cahaya Imani (International Journal of Advances in Applied Sciences, 2022)
A chemical-based insect repellent such as N, N-diethyl-3-methylbenzamide (DEET) is commonly used against all insects despite its toxicity in humans. Hence, a repellent agent from natural sources of plant essential oil was introduced. Some of the plants which have the repellent potential are catnip, hairy basil, citronella, vetiver, clove, and citrus. Citronellal, citronellol, geraniol, eugenol, eugenol-acetate, and beta-caryophyllene are among the repellent active components in these plants. Citrus hystrix (kaffir lime) was known for several applications in food, health, and skincare, but its potential as mosquito repellent is still new. This overview paper highlights the potential of kaffir lime essential oil as a mosquito repellent and the encapsulation of essential oil related to mosquito repellent. Several studies on kaffir lime essential oil as mosquito repellent was conducted and revealed that the major repellent active components are citronellol and limonene. Pure kaffir lime essential oil provides one-hour repellent protection against the mosquito. However, an addition of 5% vanillin prolongs the protection time to three hours. Essential oil is easily vaporized at room temperature which shortens its effectiveness time. Encapsulation of the essential oil would control the vaporization process and hence prolong its efficiency. Nonetheless, almost no research work reported on the encapsulation of kaffir lime essential oil and the release mechanism of the encapsulated kaffir lime.